KEANDALAN MONITORING TELEKOMUNIKASI DATA MENGGUNAKAN SERAT OPTIK DALAM PENGENDALIAN OPERASI SISTEM TENAGA LISTRIK - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
Electric power systems continue to evolve as the needs of the community will also continue to increase electric power. Electrification ratio in Indonesia reached about 60%, so it still requires the development of electric power system large enough to achieve 100% electrification ratio. To control the large electric power systems as well as Java-Bali system connections necessary telecommunications facilities that are reliable and adequate for data and information needed to make operating decisions can be obtained quickly. Telecommunications facilities powerline carrier and fiber optic are the only practical means of telecommunication which is owned by PLN, particularly for optical fiber means mounted in lightning wire high voltage lines.